Pengembangan Multimedia Pembelajaran Interaktif Pada Mata Pelajaran Informatika di SMP Negeri 7 Kuningan - Sofiyah, Aas Siti; Nurjanah, Hifni Fitriah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop interactive learning multimedia based on Smart Apps Creator (SAC) as a solution to the lack of engaging and interactive media in informatics learning at SMP Negeri 7 Kuningan. The development method used was the APPED (Analysis, Planning, Production, Evaluation, Dissemination) model. The research subjects were 40 seventh-grade H students. Data collection techniques included observation, interviews, and questionnaires. Data were analyzed descriptively quantitatively. Validation was conducted by media experts and subject matter experts. The results showed that this interactive learning media was highly effective based on alpha and beta testing, with an average score of 88% (categorized as "Very Effective"). Student response to the media was also high, with a percentage of 86% (categorized as "Very Good").